2001
DOI: 10.1002/1097-4571(2000)9999:9999<::aid-asi1055>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

The role of user profiles for news filtering

Abstract: Most online news sources are electronic versions of "ink-on-paper" newspapers.These are versions that have been filtered, from the mass of news produced each day, by an editorial board with a given community profile in mind. As readers, we choose the filter rather than choose the stories. New technology, however, provides the potential for personalized versions to be filtered automatically from this mass of news on the basis of user profiles.People read the news for many reasons: to find out "what's going on",… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As an example of these efforts, Watters and Wang () extract feature phrases from news content. However, it seems that people prefer a combination of personalization and serendipitous content (Shepherd, Duffy, Watters, & Gugle, ), indicating, perhaps, that audiences are interested in new types of content or tire when being exposed to the same topics over time. Therefore, efforts have also focused on modeling audience preferences over time, including efforts based on similarity among audience members (Lv, Meng, & Zhang, ) or specific aspects of the content, such as entity identification (Zhang, Boons, & Batista‐Navarro, ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…As an example of these efforts, Watters and Wang () extract feature phrases from news content. However, it seems that people prefer a combination of personalization and serendipitous content (Shepherd, Duffy, Watters, & Gugle, ), indicating, perhaps, that audiences are interested in new types of content or tire when being exposed to the same topics over time. Therefore, efforts have also focused on modeling audience preferences over time, including efforts based on similarity among audience members (Lv, Meng, & Zhang, ) or specific aspects of the content, such as entity identification (Zhang, Boons, & Batista‐Navarro, ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…those that have exploited the media the most. To further describe the genre as a base for the forthcoming longitudinal study, we used the visual pattern [8] and the definition of broadsheet metaphor [19]. Schmid-Isler [8] divides the visual pattern of a traditional newspaper front page into: a) the name of the newspaper -the brand, b) the number of columns, c) headings, d) photographs and e) table of contents (often to the left).…”
Section: Figure 2 the Column And Section Gridmentioning
confidence: 99%
“…The broadsheet metaphor is described as "a newspaper layout of text and photographs… integrated into a coherent presentation" [19, p.151]. When referring to the broadsheet metaphor we include both the descriptions of Schmid-Isler [8] and Shepherd et al [19].…”
Section: Figure 2 the Column And Section Gridmentioning
confidence: 99%
“…In addition, interest profiles may change over time. It has been shown that interest profiles explicitly contributed by users often result in less accurate document selection than stereotyped interest profiles (Shepherd et al, 2001;Kuflik et al, 2003). A body of research exist that address the problem of automatic generation of interest profiles from users' (explicit or implicit) relevance feedback on some selected documents.…”
Section: Related Workmentioning
confidence: 99%